«FROM LIVING SCENES, THESE PALLIED NOTES...»: ON ENGLISH TRANSLATIONS OF «EUGENE ONEGIN» BY A.PUSHKIN - Nesterova, N.M. (Perm Federal Research Centre Journal, 2015)
The paper is devoted to the "untranslatability" of A.S. Pushkin’s novel in verse "Eugene Onegin» and to the reasons causing this untranslatability. The article focuses on the history of translation of Pushkin’s work into English which counts about 40 English-language versions of «Eugene Onegin». Two different methods of translation, known in the translation studies as foreignization and domestication, as well as the verse and prose translations of Pushkin’s text are considered.